Pendampingan Komunitas Studi Tafsir Al-Qur’an di PP. Tahfidz Ribathul Qur’an wa Qiraat Malang: Model Pemberdayaan Berbasis Community of Practice (CoP) - Sa’adah, Faridatus; Ertanti, Devi Wahyu; Santoso, Kukuh (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This study examines the effectiveness of integrating a Community of Practice (CoP) with Participatory Action Research (PAR) to develop a Qur’anic Tafsīr Study Community at PP. Tahfidz Ribathul Qur’an wa Qiraat, Karangbesuki, Sukun, Malang. The scope covers the articulation of the knowledge domain, community governance, and the development of pedagogical artifacts. A qualitative PAR design was implemented in three cycles (plan–act–observe–reflect). Participants included six teachers and twelve students; data were gathered through in-depth interviews, participant observation, and documents (modules, session summaries, assessment rubrics). Data were thematically analyzed with iterative verification and member checking during reflective forums. Findings indicate: (1) a clarified domain and rotating roles (moderator, presenter, reference editor, note-taker) fostered meaningful participation; (2) reference literacy and argument structure improved through a shared formative rubric; (3) pedagogical artifacts—a micro-curriculum, study guidelines, rubric, and a shared artifact bank—supported continuity; (4) the integration of ḥifẓ and tafsīr emerged as a distinctive learning outcome; and (5) constraints in literacy and time were mitigated via senior–junior pairing, reading clinics, and time-boxing. In conclusion, the CoP–PAR model effectively strengthens collaborative, standards-based, and sustainable tafsīr practice and is suitable for replication. Future work should include longitudinal studies across semesters and lightweight digital platforms to archive artifacts and enable structured peer feedback.